Enigma of the cholesterol paradox in acute myocardial infarction: lessons from an 8-year follow-up of all-cause mortality in an age-matched and sex-matched case–control study with controls from the patients’ recruitment area - Göran Nilsson; John Öhrvik; Jerzy Leppert (BMJ Open)
Objective To assess the impact of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) on long-term all-cause mortality (ACM) in patients with acute myocardial infarction (AMI) and controls.Design Matched case–control study with 8-year follow-up.Setting Vastmanland County Hospital, Vasteras, Sweden.Participants Consecutive patients with AMI admitted to the coronary care unit from March 2005 to May 2010 and age-matched and sex-matched controls from the general population.Outcome measures ACM.Results Person-year at risk among patients with AMI and controls was 11 667 (cases: 5780 and controls: 5887). During follow-up, 199 patients and 84 controls died, implying 3.4 deaths among patients and 1.4 among controls per 100 person-years at risk. Unadjusted Cox analyses showed significantly increasing mortality by decreasing TC and LDL-C levels in both patients (HR=0.70, 95% CI 0.62 to 0.79, p<0.001, and HR=0.64, 95% CI 0.56 to 0.74, p<0.001) and controls (HR=0.73, 95% CI 0.60 to 0.89, p=0.002, and HR=0.74, 95% CI 0.59 to 0.93, p=0.010). After adjusting for clinical variables, the results for the patients remained significant. Cox analyses of the relations between mortality and TC and LDL-C below and above their respective medians revealed the following pattern. Patients: below medians were TC and LDL-C levels significantly inversely related to mortality; above medians there were no relations with mortality. Controls: below medians were TC and LDL-C levels significantly inversely related to mortality; above medians were LDL-C levels significantly positively related to mortality. Mean LDL-C level in patients with blood sampled >12 hours after symptom onset was 0.41 mmol/L lower than that in patients with blood sampled ≤12 hours (p=0.030). This LDL-C decrease was reasonably caused by ongoing AMI and reflects the difference in LDL-C levels between patients and controls.Conclusions In patients with AMI, lower TC and LDL-C levels independently predict higher ACM. In their controls, LDL-C levels above the median independently predict higher ACM. This study adds to the body of evidence supporting the existence of a cholesterol paradox.